Antigenic relationship of Canine Parvovirus type 2c with other variants and vaccine strain using in-vitro cross neutralization assay - Kour, Hansmeet; Kaur, Gurpreet; Chandra, Mudit (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Canine parvovirus-2 (CPV-2) is a part of genus Protoparvovirus and is known to cause acute viral infection in domestic canines. Dogs of any age group may invariably be affected by CPV which can cause up to 100% morbidity and 10–91% mortality. The difference in amino acid sequences over the capsid protein VP2 of CPV-2 has resulted in the emergence of several variants, namely CPV-2a, CPV-2b, CPV-2c. Recently, two new variants are reported- new CPV-2a and new CPV-2b. Prevention of CPV infection rely upon vaccination and, being core vaccines, are included in the vaccination schedule of dogs irrespective of the geographical location. Despite the in-depth vaccination program adopted worldwide, CPV infections are one of the major causes of infection and death in young dogs. The recent trends of vaccine failure throughout the world have raised questions about the effectiveness of the old type vaccine (CPV-2 based) against all the antigenically different strains especially CPV-2c. The present study aimed at establishing antigenic relationship of CPV-2c and other variants by invitro Cross Neutralization Assay. The results of neutralization assay indicated that the serum of CPV 2c could neutralize the homologous type of virus at a much higher titre than the heterologous virus types. In addition to this, the vaccine strain was also found to show less titre against CPV-2c virus type. Thus, it could be concluded that the vaccine strain of CPV provides less protection to the dogs for the CPV 2c type.